Anatomical variation analysis of left upper pulmonary blood vessels and bronchi based on three-dimensional reconstruction of chest CT - Deng, Youjun; Cai, Songhua; Huang, Chujian; Liu, Wenyi; Du, Longde; Wang, Chunguang; Jia, Ran; Lin, Shengcheng; Yu, Xin; Yu, Xiangyang; Yang, Yikun; Yang, Chenglin; et al. (Frontiers in Oncology, 2022)
Background With its growing popularity and potential outcome, preoperative three-dimensional reconstruction of chest computed tomography (CT) has been widely used in video-assisted thoracic surgery (VATS) segmentectomy for treating non-small cell lung cancer (NSCLC). This study aimed to summarize the experience of anatomical variation analysis of left upper pulmonary blood vessels and bronchi based on the three-dimensional reconstruction of chest CT. Materials and Methods A total of 103 patients with early-stage NSCLC were chosen to undergo VATS segmentectomy based on preoperative three-dimensional reconstruction of chest CT in our institute from September 2019 to July 2022. Data such as clinical characteristics and variations in blood vessels and bronchi were reviewed in this study. Results The branches of the left lingual pulmonary artery may mutate into the LS1 + 2 + 3. A1 + 2 has four subtypes. The distribution of variation is relatively balanced, and the most common variation is type I (35/103, 33.9%). Most lingual arteries originate from the oblique cleft side of the lingual bronchus (79/103,76.7%). Most V(1 + 2)c* are small developments (70/103, 68.0%). The venous return of the proper segment mainly depends on V(1 + 2)b + c. The variation in the left upper lobe bronchus is complex. The most common variant is the bifurcation type (type A to G, 92/103, 89.3%) and bifurcation type A (62/103, 60.2%). The posterior apical segment artery of the left upper lung is not accompanied by its bronchus. Conclusions The variation types of blood vessels and bronchus in the upper lobe of the left lung are complex. Preoperative CT-based three-dimensional reconstruction of pulmonary arteries, veins, and bronchi is of great significance. It can help understand the variations, accurately locate lesions before the surgery, and effectively plan surgeries.